Evaluation of the urodynamic and hemodynamic effects of orally administered phenylpropanolamine and ephedrine in female dogs - Carofiglio, F; Hamaide, A.J; Farnir, F; Balligand, M.H; Verstegen, J.P (American journal of veterinary research, 2006)
Objective-To compare the urodynamic and hemodynamic effects of different dosages of phenylpropanolamine and ephedrine and determine effective dosages in increasing urethral resistance in female dogs. Animals-20 sexually intact female Beagles. Procedure-Dogs were allocated into 4 groups and received phenylpropanolamine once, twice, or 3 times daily, or ephedrine twice daily, for 14 days. On days 0, 7, and 14, urethral pressure profiles were performed while dogs were anesthetized with propofol. Variables recorded included maximum urethral pressure, maximum urethral closure pressure, integrated pressure, functional profile length, anatomic profile length, plateau distance, distance before maximum urethral pressure, and maximum meatus pressure. Arterial and central venous pressures were measured before anesthetic induction and 10 and 35 minutes after induction. Results-Administration of phenylpropanolamine once daily or ephedrine twice daily significantly increased maximum urethral pressure and maximum urethral closure pressure. Values for integrated pressure were significantly increased after 14 days of once-daily administration of phenylpropanolamine. Variables did not change significantly from day 7 to day 14. Diastolic and mean arterial blood pressures increased significantly during the treatment periods, and arterial pressure decreased during propofol infusion. Conclusions and Clinical Relevance-Oral administration of phenylpropanolamine once daily or ephedrine twice daily increased urethral resistance in clinically normal dogs and may be recommended for management of urethral sphincter mechanism incompetence. Treatment efficacy may be assessed after 1 week. Dogs with concurrent cardiovascular disease should be monitored for blood pressure while receiving alpha-adrenergic agents because of the effects on diastolic and mean arterial pressure.